1983
DOI: 10.1136/ard.42.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis complicating systemic lupus erythematosus

Abstract: Active systemic lupus erythematosus in a 32-year-old Chinese woman was successfully controlled by plasmapheresis and steroids. However, occult visceral leishmaniasis was uncovered during therapy and responded to appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 2 publications
1
7
0
1
Order By: Relevance
“…These patients experienced relapses of VL despite therapy with amphotericin. VL was diagnosed in a woman with lupus on steroids who developed VL five years after living in Hong Kong and was suspected of having activation of latent disease in the setting of immunosupression [Wallis and Clark, 1983]. …”
Section: Visceral Leishmaniasis During Usage Of Immunomodulatory Agenmentioning
confidence: 99%
“…These patients experienced relapses of VL despite therapy with amphotericin. VL was diagnosed in a woman with lupus on steroids who developed VL five years after living in Hong Kong and was suspected of having activation of latent disease in the setting of immunosupression [Wallis and Clark, 1983]. …”
Section: Visceral Leishmaniasis During Usage Of Immunomodulatory Agenmentioning
confidence: 99%
“…Recent reports have indicated that spontaneously controlled (subclinical) infections caused by the intracellular protozoan, Leishmania donovani, may reactivate in immunocompromised patients (1)(2)(3)(4)(5)(6)(7). In addition, primary treatment Receivedfor publication 27 May 1988 and in revisedform 18 November 1988. failures using ordinarily effective pentavalent antimony (e.g., sodium stibogluconate, or Pentostam [proprietary name of Burroughs Wellcome]) as well as prompt relapses have also been described in Leishmania donovani-infected patients who have AIDS or are receiving immunosuppressive agents (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition of Leishmania infection in patients with SLE is essential because intense immunosuppression may transform visceral leishmaniasis into a rapidly progressive disease. This is very dif cult to treat with the current antiparasitic therapy and eventually leads to a fatal outcome, as occurred in two of the ve patients reported in the English language literature (3)(4)(5)(6). A high index of suspicion is necessary for an early diagnosis because fever and pancytopenia are also common in active SLE and, as in our observation, the two other typical features of leishmaniasis, hepatosplenomegaly and hypergammaglobulinaemia, may be absent.…”
mentioning
confidence: 49%